Prosperity through Tourists in Lamjung District: An Anthropological Outlook - Bhatta, Badri Nath (Interdisciplinary Research in Education, 2019)
The study areas of anthropology have been growing day by day. Therefore, it has concerned with various parts of society such as sanitation, water supply, poverty, traditional practice, folk music, tourism etc as multidisciplinary areas. In fact, anthropology and tourism are co-evolutionary process in the path of their developments because they help each other in many ways. Traditionally, tourism and tourist are major anthropological sources of information to analyse the situation of then and present society and culture. Similarly, tourist can enjoy visiting any places by learning anthropological knowledge and findings. Methodologically, this is based on field observation, interview and other secondary sources to analyse the scenario. After the introduction of democracy in Nepal, she has been opened to outsiders. As a result, Sir Edmund Hillary as foreigner visited Nepal. Hillary with Tenzing Norgy Sherpa successfully climbed the Mount Everest in 29 May, 1953 at the first time. Then the glorious name of Nepal has become famous in the world. The tourism industries have been initiated from Thamel, Solukhumbo, Pokhara and then gradually extended in other parts of the country. Tourism at present period has popular pursuit in several parts of Nepal involving from hotel, lodge, guide, restaurant, expedition to home stay and other businesses. Lamjung has own identity in tourism perspective. The Ghalegaun is famous in SAARC level as model program for the home stay concept. From perennial snow peaks, biodiversity to natural forest of rhododendron in mountain to hill parts in the north and plain narrow valley in the south to develop cultural lives can be observed there. Lamjung has been enriched in different culture, fest and festivals. Paudure dance among the Kumal, bees hunting in steep slope rocky hills to Rodi in the Gurung have their own identity popular in the district.